Development of Polyhouse Solar Dryer for Drying Granular Jaggery - Sreedevi, P.; Veerabhadrarao, K.; Jamuna, P.; Rao, P. V. K. Jaganadha (International Journal of Bio-resource and Stress Management, 2021)
Jaggery is a traditional Indian sweetener prepared from sugarcane juice through evaporation process and is considered as medicinal sugar due to its nutritional and thereupatic properties. To improve the shelf-life of solid jaggery , making jaggery in the form of granules with moisture content of 1–2% was recommended.A Polyhouse solar dryer for drying granular jaggery with a capacity of 200 kg was developed at Regional Agricultural Research Station, Anakapalle, Andhra Pradesh, India. Traditionally, granular jaggery was dried in openyard resulting in contamination with dust, insects, birds and rain. A comparative study was carried for drying granular jaggery with initial moisture of 9.3 to 10.5% (db) in both polyhouse solar dryer and in an open yard during the month of March– April, 2019. The study revealed that the rate of drying was faster in poly house compared to open yard drying. The temperature inside the polyhouse dryer was 59% higher than the ambient conditions. The percent saving in time for drying of granular jaggery in poly house dryer was 38% to attain optimum moisture content of 1.7% for stable shelf life besides maintaining hygienic conditions. The quality parameters of jaggery in terms of sucrose and reducing sugars percentage showed insignificant changes in both methods. However, the color of the granular jaggery was well retained in polyhouse dryer compared to open yard drying. Hence, this study will be helpful for small and micro entrepreneurs for large scale drying of granular jaggery under hygienic conditions utilizing renewable energy resources.